Informative writing : your practical guide to effective communication - Goddard, Kenneth W. (Kenneth William) (London ; Herndon, VA : Cassell, 1998)
This book offers a step-by-step methodology for delivering concise, precise and readable documents honed with a particular readership in mind for writing informative.
Keywords: English language; Rhetoric; Report writing; Rhetoric exposition; Exposition (Rhetoric); Report writing; English language -- Rhetoric